2012
DOI: 10.1002/aenm.201200204
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Transparent Tandem Organic Solar Cells with 90% Internal Quantum Efficiency

Abstract: Semi‐transparent (ST) organic solar cells with potential application as power generating windows are studied. The main challenge is to find proper transparent electrodes with desired electrical and optical properties. In this work, this is addressed by employing an amphiphilic conjugated polymer PFPA‐1 modified ITO coated glass substrate as the ohmic electron‐collecting cathode and PEDOT:PSS PH1000 as the hole‐collecting anode. For active layers based on different donor polymers, considerably lower reflection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 42 publications
2
89
1
Order By: Relevance
“…Thus, building tandem architecture www.advenergymat.de by introducing multiple photoactive materials allows fine adjustment of absorption, transparency and efficiency of the devices. [169] Tang et al [170] enhanced PCE of the semitransparent OSCs by connecting the stacked two semitransparent sub-cells in parallel. The total loss of photons from reflection, parasitic absorption, and transmission in the semitransparent tandem solar cell could be smaller than the loss in a single device using the same photoactive materials.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…Thus, building tandem architecture www.advenergymat.de by introducing multiple photoactive materials allows fine adjustment of absorption, transparency and efficiency of the devices. [169] Tang et al [170] enhanced PCE of the semitransparent OSCs by connecting the stacked two semitransparent sub-cells in parallel. The total loss of photons from reflection, parasitic absorption, and transmission in the semitransparent tandem solar cell could be smaller than the loss in a single device using the same photoactive materials.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…There are several organic-based approaches that produce semi-transparent OPV devices that exhibit good electrical performance (Figure 8), whereby they are composed of organic electronic materials, and transparent electrodes based on a wide range of different materials, including conducting polymers [122][123][124][125], thin metal films [126], sputtered transparent conducting oxides of LiCoO2/Al [127], carbon nanotubes [122], graphene [128], and silver nanowires (Ag NWs) [129][130][131][132][133]. Recently, a study by Beiley et al [134], has shown the development of a semi-transparent OPV which consists of a silver nanowire (Ag NW) and zinc oxide nanoparticle (ZnO NP) composite top electrode, and has a power conversion efficiency of 5.0%.…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%
“…On the other hand, the limited harvesting at all wavelengths resulting from the low reflectivity of the top electrode can be partially compensated with the incorporation of an additional absorber layer in a tandem configuration. [82][83][84][85] The second approach to increase transparency in the visible spectrum and to limit the loss in PCE is the incorporation of multilayer anti-reflection coatings for the visible or Bragg reflectors to help to trap the near UV and NIR. 41,42,[86][87][88][89][90] The combination of both may further improve the balance between transparency and PCE.…”
Section: Introductionmentioning
confidence: 99%